Analisis pengaruh pertumbuhan penjualan dan rasio profitabilitas terhadap harga saham pada perusahaan di Bursa Efek Indonesia - Vivi Widiyanti; Anggun Permata Husda (eCo-Buss, 2022)
This study was conducted with the aim to examine the effect of sales growth and profitability ratios on stock prices in real estate/property sector companies that listed in the Indonesia Stock Exchange for the period 2016 to 2020. The independent variable in this study are sales growth and profitability ratio using return on equity measurement, while the dependent variable in this study is stock price. The sampling technique that used in this study is purposive sampling technique where the population of companies in this study are 79 companies and 9 companies that have been selected as samples to be used in accordance with predetermined criteria. Data analysis in this study consisted of descriptive statistic, classic assumption test, multiple linear regression analysis and hypothesis test proceed by SPSS (Statistical Product and Service Solutions) Program Version 28. Based on the results of hypothesis test using t test showed that sales growth and return on equity has not a significant effect on stock price.Based on the result of hypothesis test using f test showed the significant value 0,305 > 0,05 so both of sales growth and return on equity have not a significant effect of stock price.